Pengaruh Pemanfaatan Model PjBL Berdiferensiasi Terhadap Hasil Belajar Matematika Materi Statistika Kelas VI SDN Gondang 1 - Akbar Dakha Prabowo (PGSD Universitas Muhammadiyah Cirebon, 2025)
Statistics learning at elementary school level often faces difficulties in conveying abstract concepts. One approach that can improve students' understanding is the application of project-based learning (PjBL) with differentiation. This study aims to test the effect of the differentiated PBL model on Statistics material on student learning outcomes in grade VI of SDN Gondang 1. This study uses a quantitative pre-experimental approach with a one group pretest-posttest design. The sample was selected using a simple random sampling technique that obtained 31 students as the experimental group. The instruments given were pre- and post-learning tests. Data were analyzed using paired sample t-tests and n-gain to measure improvements in students' understanding. The results of the paired sample t-test showed a significant difference between the pretest and posttest scores, with a significance value of 0.000, indicating that the differentiated PjBL model is effective in influencing the learning outcomes of statistical concepts. However, based on the n-gain calculation, the increase in students' average scores of 19.19% is included in the low category. Although there was a significant increase, these results indicate that the implementation of the differentiated PBL model requires further strengthening to improve its effectiveness. Keywords: Differentiated PBL, Learning Outcomes, Statistics